Low-Frequency Low-Intensity Ultrasounds Do Not Influence the Survival and Immune Functions of Cultured Keratinocytes and Dendritic Cells. (1st December 2009) - Scarponi, Claudia; Nasorri, Francesca; Pavani, Francesca; Madonna, Stefania; Sestito, Rosanna; Simonacci, Marco; De Pità, Ornella; Cavani, Andrea; Albanesi, Cristina
Abstract : Low-frequency ultrasounds (US) are used to enhance drug transdermal transport. Although this phenomenon has been extensively analyzed, information on US effects on the single skin cell components is limited. Here, we investigated the possible effects of low-frequency US on viability and immune functions of cultured human keratinocytes and dendritic cells (DC), skin cells involved in the regulation of many immune-mediated dermatoses. We demonstrated that US, employed at low-frequency (42 KHz) and low-intensity (0.15 W / cm 2 ) values known to enhance drug and water transdermal transport, did not affect extracellular-signal-regulated-kinase (ERK)1/2 activation, cell viability, or expression of adhesion molecules in cultured keratinocytes. Moreover, US at these work frequency and intensity did not influence the keratinocyte expression and release of immunomodulatory molecules. Similarly, cultured DC treated with low-frequency low-intensity US were viable, and did not show an altered membrane phenotype, cytokine profile, nor antigen presentation ability. However, intensity enhancement of low-frequency US to 5 W / cm 2 determined an increase of the apoptotic rate of both keratinocytes and DC as well as keratinocyte CXCL8 release and ERK1/2 activation, and DC CD40 expression. Our study sustains the employment of low-frequency and low-intensity US for treatment of those immune skin disorders, where keratinocytes and DC have a pathogenetic role.